Dashboard Pemantauan Inventori Pada Mixue Erlangga Simpang Lima Berbasis Web - Jaya, Theofilus Palaun; Prihati, Yani; Gondohanindijo, Jutono (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This research aims to develop a web-based inventory monitoring dashboard for Mixue Erlangga Simpang Lima. The dashboard is designed to provide ease in monitoring and managing stock in real-time, thereby enhancing operational efficiency and reducing the risk of stockouts or overstocking. The research methodology includes needs analysis, system design, development, and application testing. The result of this research is a dashboard that can display inventory data visually and interactively, and provide notifications when stock levels approach predefined minimum or maximum limits. The implementation of this dashboard is expected to assist management in making quicker and more accurate decisions regarding inventory management. User evaluations indicate that this dashboard successfully improves efficiency and effectiveness in monitoring and managing stock at Mixue Erlangga Simpang Lima.